The Effect of Hurdles and Speed Jumping Training on the Increase in the Long Jump Squat Style of Class VII Students of SMP Madinul Ulum Tungkal Jaya, Musi Banyuasin Regency - Sulurudin, Sulurudin; Lian, Bukman; Putri, Siti Ayu Risma (Journal of Social Work and Science Education, 2023)
The purpose of this study was the effect of hurdles training and long jump speed in the squat style of SMP Madinul Ulum Tungkal Jaya, Musi Banyuasin Regency. This research was conducted at Madinul Ulum Tungkal Jaya Middle School, Musi Banyuasin Regency, which is located on Jl. Poros Sri Damai No. 6 Rt. 19 Dusun VI, Like Peace, Kec. Tungkal Jaya, Kab. Musi Banyuasin Province of South Sumatra. The method used in this study is an experimental method with a one group pre-test and post-test design. The data collection technique uses the long jump test technique. The population of this study were all students of class VII at Madinul Ulum Tungkal Jaya Middle School, Musi Banyuasin Regency, while there were students of class VII.2 and VII.3 with a total of 62 people. The data analysis technique used is the inferential data analysis technique with the help of the t test SPSS version 23.00 for windows. Based on the discussion that has been stated above, it can be concluded that: (1) there is an effect of hurdles training on the squat style long jump; (2) Effect of speed training on long jump squat style.